Risk factors for surgical site infection in potentially contaminated surgeries (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To associate the intraoperative period risk factors of potentially contaminated surgeries with the occurrence of surgical site infection in the postoperative period at the hospital and at domicile. Method: A longitudinal, descriptive and quantitative study was realized from February to June 2015 with 90 patients and with an interview and observation script applied during the surgical procedure. Results: The surgical site infection occurred in nine participants in the postoperative hospital and 42 in the domicile. Conclusion: Hospital and domicile control and follow-up are suggested, preventing the risk of infections and making patient safety possible.
Keywords: Stomatherapy; Patient safety; Intraoperative period; Surgical wound infection; Hospital infection